Corporate Social Responsibility and Kinerja Keuangan - Nurazizah Nurazizah; Tresyca Ramadhini; Dhina Rahma Juliyanti; Abraham Koto; Rinavia Arlita (Journal of Student Research, 2025)
This study aims to synthesize the results of previous research on Corporate Social Responsibility (CSR) and Financial Performance through Systematic Literature Review (SLR). This research using SLR presents quantitative data to determine the development of CSR and Financial Performance issues. There are several parameters used, namely journal sources, variable mapping and theory and type of company, research approach. The results of this study show that there are 30 articles originating from accredited national and national journals during the period 2020-2024. Stakeholder theory is the most widely used theory and the use of quantitative methods is dominant in CSR and financial performance. Manufacturing companies are the most widely researched companies on CSR and financial performance issues. This study contributes significantly to the map of previous research in a structured manner in the form of a list of independent, dependent, moderating, and mediating variables as determinants, consequences, and moderation-mediation so that through the relationship map, this study provides input for CSR topics that still need to be explored. This study has limitations in that it is an interpretive study, so the findings are limited to the researcher's interpretation of the results of the literature review. Other researchers who conduct the same literature review may have different interpretations. In addition, the CSR study in this study only focuses on the field of management accounting so that other fields such as taxation and financial accounting need to be further explored in order to obtain a more comprehensive literature study.